The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12603-009-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: Clinical evaluation, biological markers and other evaluation tools

Abstract: Sarcopenia is characterized by a lower skeletal muscle quantity, higher fat accumulation in the muscle, lower muscle strength, and lower physical performance. The most commonly used, low cost and accessible methods to assess skeletal muscle mass include dual energy X-ray absorptiometry (DEXA), anthropometry and bioelectrical impedance analysis (BIA). Magnetic resonance imaging (MRI), computerized tomography (CT) and creatinine excretion are the most specific golden standards for assessing muscle mass or cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 59 publications
(57 reference statements)
3
134
0
6
Order By: Relevance
“…5,6,14 Although sarcopenia is primarily a disease of the elderly, it is known that decreased muscle mass may be associated with several conditions other than the aging process, and can also be seen in younger patients, such as those with inflammatory diseases. 10 In the present study, the SMI of the patients with RA was found to be lower than the controls regardless of the ages of the participants. Thus, lower lean muscle mass may be associated with disease itself rather than age profile.…”
Section: Smisupporting
confidence: 41%
See 1 more Smart Citation
“…5,6,14 Although sarcopenia is primarily a disease of the elderly, it is known that decreased muscle mass may be associated with several conditions other than the aging process, and can also be seen in younger patients, such as those with inflammatory diseases. 10 In the present study, the SMI of the patients with RA was found to be lower than the controls regardless of the ages of the participants. Thus, lower lean muscle mass may be associated with disease itself rather than age profile.…”
Section: Smisupporting
confidence: 41%
“…It has been reported that it provides valid estimates of appendicular skeletal muscle mass, and skeletal muscle measures with DXA are associated with prevalent and incident physical disability. 10 To define presarcopenia, it is necessary to have a measure of relative muscle mass. Various options to define subnormal values for muscle mass designation have been suggested.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the size of trunk muscle are thought to best reflect log-term chronic illness and systemic health (3,13,15).…”
Section: Original Articlementioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is a simple method that has also been used despite its lack of accuracy. While imaging diagnostic modalities such as magnetic resonance imaging (MRI) or computed tomography (CT) allow for accurate measurements of muscle mass, these methods are cost prohibitive [56][57][58] .…”
Section: Diagnosis and Treatment For Sarcopeniamentioning
confidence: 99%
“…The relationship between biomarkers and sarcopenia has been reported 57,58,62) , and the usefulness of measuring several biomarker candidates, including inflammatory biomarkers, clinical parameters, hormones, and products of oxidative damage, has been studied. Biomarkers that can be obtained from blood and urine may be beneficial, as there is little burden on the patient.…”
Section: Diagnosis and Treatment For Sarcopeniamentioning
confidence: 99%